2012
DOI: 10.1007/s00345-012-0831-3
|View full text |Cite
|
Sign up to set email alerts
|

Complications of kidney transplantation with grafts from expanded criteria donors

Abstract: Transplantation of kidneys from expanded criteria donors is associated with a significant higher risk of medical and surgical complications than kidneys from non-expanded criteria donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
18
1
2
Order By: Relevance
“…Furthermore, a study by Frezza et al [96] observed that in a long-term outcome after kidney transplantation, Glucocorticoids (GCs) resistant patients showed higher incidence of acute rejection episodes, lower acute rejection-free survival, poor response of acute rejection treatment, as well as higher incidence of renal allograft loss. However, no difference was found regarding patient mortality, wound, and vascular complications [63]. Moreover, greater frequency of more severe surgical complications and lower graft survival has been reported [63].…”
Section: Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study by Frezza et al [96] observed that in a long-term outcome after kidney transplantation, Glucocorticoids (GCs) resistant patients showed higher incidence of acute rejection episodes, lower acute rejection-free survival, poor response of acute rejection treatment, as well as higher incidence of renal allograft loss. However, no difference was found regarding patient mortality, wound, and vascular complications [63]. Moreover, greater frequency of more severe surgical complications and lower graft survival has been reported [63].…”
Section: Consequencesmentioning
confidence: 99%
“…Nemati and Taghipour [24], Barba et al [62] support that expanded criteria donors may be risk factors to graft failure. Reese et al [63] defined expanded criteria as donors who are greater than 50 years with at least hypertension history, serum creatinine >1.5 mg/dl or cause of death from cerebrovascular accident.…”
Section: Donor Related Factorsmentioning
confidence: 99%
“…Aging of the donors directly impacts on long-term graft survival, and, in a recent series, among 407 KTs, graft survival was significantly lower for the ECD when compared to the non-ECD (5-year survival rate: 74% versus 90%, < 0.001) [21]; the older the donor, the greater seems to be the decrease in survival [6]. A similar correlation between age and graft outcome has been described in living donor KT [28].…”
Section: The ''Marginal Donors''mentioning
confidence: 96%
“…The risk of graft failure (e.g., return to maintenance dialysis or graft nephrectomy) is more frequent in marginal donor kidney recipients [6,16,17], as largely documented in recently published series [20][21][22][23][24][25][26][27] (Table 1). Aging of the donors directly impacts on long-term graft survival, and, in a recent series, among 407 KTs, graft survival was significantly lower for the ECD when compared to the non-ECD (5-year survival rate: 74% versus 90%, < 0.001) [21]; the older the donor, the greater seems to be the decrease in survival [6].…”
Section: The ''Marginal Donors''mentioning
confidence: 99%
“…Thus, donor kidneys from diverse sources including the ECDs are received and transplanted [3]. However, reports indicate that kidneys sourced from ECDs are characterized by post-transplant complications such as acute rejection episodes, primary nonfunction, greater rate of delayed graft function (DGF) and greater frequency of graft failure [4]. The cold-storage and machine perfusion (MP) are two commonly employed techniques for the preservation of kidneys before transplantation [5].…”
Section: Introductionmentioning
confidence: 99%